TEOLOGI PASTORAL VIRTUAL - Agung Jaya; Daud Patana (Institut Agama Kristen Negeri Manado, 2023)
This paper describes a virtual pastoral theology that is indispensable, especially in the atmosphere of the COVID-19 pandemic. This paper uses a qualitative method with a literature study approach to take advantage of the sharing of related journals and books. The COVID-19 pandemic has forced congregation members to change their normal lifestyle to a new (virtual) era. Virtual pastoral is a relevant answer to the problems of pastoral care today. Virtual pastoral can be done by phone, facebook, video call, instagram, zoom app, google meet and so on. we need to understand that whatever pastoral/pastoral method is used should not shift the focus from shepherding itself, namely God. Virtual pastoral is a relevant answer to the problems of pastoral care today. Although using a different (virtual) method, it does not eliminate the substance of pastoral care itself. The presence of virtual pastoralists has been positively welcomed by the congregation, especially during this pandemic.